2013
DOI: 10.4315/0362-028x.jfp-12-440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticides on the Reduction of Plant and Human Pathogenic Bacteria in Application Water

Abstract: Overhead spray applications of in-field tomato treatments dissolved in aqueous solutions have specific pest targets (fungal, bacterial, insect, or other). Any organism present in the solution or on treated plant surfaces that is not a specific target of the application is unlikely inactivated and can instead be spread through the phyllosphere. In this laboratory study, commercially labeled pesticides (including Actigard 50WG, Bravo Weather Stik 6F, Cabrio 20EG, Kasumin, Kocide 3000 46WG, Oxidate 27L, Penncozeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…A previous study indicated that copper has antibacterial effects against Salmonella (Zhu, Elguindi, Rensing, & Ravishankar, 2012); however, in the study reported here, the application of copper hydroxide did not result in a significant reduction of Salmonella concentrations on leaf surfaces (Table 1). This finding is supported by existing literature evaluating the use of copper-based compounds against epiphytic Salmonella populations ( Mahovic et al, 2013;Ottesen et al, 2015). In contrast, Salmonella concentration had a significant log reduction in the ground leaves after copper hydroxide treatment, compared to the control (0.79 ± 0.16, p ≤ 0.05).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A previous study indicated that copper has antibacterial effects against Salmonella (Zhu, Elguindi, Rensing, & Ravishankar, 2012); however, in the study reported here, the application of copper hydroxide did not result in a significant reduction of Salmonella concentrations on leaf surfaces (Table 1). This finding is supported by existing literature evaluating the use of copper-based compounds against epiphytic Salmonella populations ( Mahovic et al, 2013;Ottesen et al, 2015). In contrast, Salmonella concentration had a significant log reduction in the ground leaves after copper hydroxide treatment, compared to the control (0.79 ± 0.16, p ≤ 0.05).…”
Section: Resultssupporting
confidence: 83%
“…Copper hydroxide is a widely used pesticide labeled to suppress levels of several bacterial and fungal diseases in tomatoes. Copper‐containing materials are broad spectrum, multi‐site, and active on bacterial pathogens through disruption of cellular proteins and enzymes, such as aggregation of ROS‐independent protein and inhibition of peptidoglycan LD‐transpeptidases (Baena, Marquez, Matres, Botella, & Ventosa, 2006; Mahovic, Gu, & Rideout, 2013; Ritchie, 2004). Acibenzolar‐ S ‐methyl stimulates the plant's natural defenses through mimicking the natural systemic activated resistance (SAR) response, which allows the host plant to ward off infection from certain bacterial and fungal pathogens (Graves & Alexander, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorothalonil (Bravo) had no significant effect on either of the pathogens. Such results are in agreement with those reported by Mahovic et al . but different from the results of Guan et al .…”
Section: Discussionsupporting
confidence: 67%
“…Current protective measures rely on chemical control, producing bactericide-resistant pathogens and other undesirable environmental consequences [22]. Alternative strategies must be found to protect A. konjac crops from Erwiniae pathogens.…”
Section: Discussionmentioning
confidence: 99%